Index analysis of technical-tactical preparedness of Olympic Games 2008 judo champions (men) - Tabakov, S. (1st International scientific conference: Exercise and quality of life, Novi Sad. March 26/28th 2009, 2009)
In the present research parameters of technical-tactical readiness of Olympic Games-2008 champions in judo (men) in all weight categories have been defined. More than 200 competitive fights in seven weight categories were analyzed.